Construction and validation of the sleep ethogram - Qiongfang Cao; Xinyu Pan; Huan Li; Haiqi Xiang; Fan Xu (Brain-Apparatus Communication)
Aims Poor sleep quality can seriously impact public health, as it can induce several chronic or acute cardiovascular and cerebral diseases. Electrophysiology is the main tool used for evaluating sleep quality; however, the precise behaviors during the whole sleeping process remain unclear.Methods Herein, we recruited 38 healthy adult men and placed them in a quiet room during the night so as to record all their sleeping behaviors with an infrared camera. Among them, 8 subjects were subjected to 36 h of acute sleep deprivation. Next, the sleep ethogram was constructed and validated by video clips. All behaviors were coded via Observer XT (Noldus software), and the detailed behavior count frequency was measured and compared.Results The results revealed significant differences in the frequency of head movement (Friedman=75.67, p<0.01), left-hand movement (Friedman=109.11, p<0.01), right-hand movement (Friedman=89.86, p<0.01), left leg movements (Friedman=96.16, p<0.01), right leg movements (Friedman=111.98, p<0.01), body movements (Friedman=95.71, p<0.01), facial movements (Friedman=97.65, p<0.01), other movements (Friedman=61.71, p<0.01) and sum number (Friedman=87.17, p<0.01) at every hour during a normal sleep period, the proportion of left hand (Friedman=14.54, p=0.04), left leg (Friedman=23.35, p<0.01), right leg (Friedman=26.68, p<0.01), and head movements (Friedman=17.61, p<0.01) were significantly different in each hour.Conclusion The proposed sleep behavior ethogram can describe behaviors occurring during the sleep process in detail. The proportion and duration of every behavior can be calculated to objectively reflect the sleep quality.